Museum exhibition : theory and practice - Dean, David (Heritage, 1994)
Museum Exhibition: Theory and Practice is the only textbook of its kind to consider exhibition development from an integrated approach from theory to practice. This comprehensive study covers a wide range of exhibition development concerns, including planning and design of exhibitions, collection care of exhibits, exhibition evaluation and administration, content and text development for exhibitions and computer usage. It provides a complete outline for all those concerned with providing displays for museums and similar cultural heritage contexts.